Health Education on Vaginal Discharge in Adolescents in Pargarutan Jae Village in 2025 - Siregar, Rya Anastasya; Harahap, Maryam Latifah; Siregar, Rahmah Juliani; Heriansyah, Rizka; Endang, Tapi; Batubara, Novita Sari (PT Inovasi Pratama Internasional, 2025)
Vaginal discharge is a reproductive health issue among adolescents, particularly among women. Vaginal discharge in adolescents requires special attention. If left untreated, it can lead to serious health problems. Vaginal discharge is normal. It occurs before menstruation. It is within normal limits as long as it is clear or translucent, odorless, non-itchy, and not excessive in quantity. The purpose of this community service program is to provide knowledge about vaginal discharge to adolescent girls. The sample consisted of 18 adolescent girls in Pargarutan Jae Village, Padangsidimpuan. The results of this community service program indicate that health education regarding vaginal discharge for adolescent girls can have a positive impact on their personal hygiene, as seen before and after the education. The conclusion is that education about vaginal discharge is essential for adolescent girls to maintain personal hygiene and prevent cervical cancer.